2021
DOI: 10.15294/ujph.v10i2.38096
|View full text |Cite
|
Sign up to set email alerts
|

Does Health Insurance Affect the Completeness of Antenatal Care?

Abstract: The antenatal treatment has been ineffective in reducing maternal mortality. Therefore, this study aimed to examine  health insurance effect on Indonesia's antenatal care quality. The 2017 Indonesian Demographic and Health Survey data were processed. Moreover, a sample size of 15,351 participants was selected using the analysis unit of study for women aged 15 to 49. In the final stage, Binary Logistic Regression was used, while other variables examined besides antenatal treatment included health insurance, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…The likelihood of intrapartum/delivery care at a medical facility increases with decreasing parity. The findings are consistent with earlier research that shows the smaller the number of parity, the more people will have to check their pregnancy in health services [ 49 , 50 ]. A survey in Ethiopia also showed that women's parity of 1–2 who intend not to have any more children would do intrapartum/delivery care in health services and get family planning services to prevent pregnancy [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…The likelihood of intrapartum/delivery care at a medical facility increases with decreasing parity. The findings are consistent with earlier research that shows the smaller the number of parity, the more people will have to check their pregnancy in health services [ 49 , 50 ]. A survey in Ethiopia also showed that women's parity of 1–2 who intend not to have any more children would do intrapartum/delivery care in health services and get family planning services to prevent pregnancy [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…The critical objective of the health insurance scheme is to empower the community based on cooperation [ 34 ]. Indonesia’s UHC scheme is the largest single-payer scheme globally, covering 203 million individuals, thereby improving coverage, use, and delivery efficiency of health services [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This health insurance is vital for managing health risks and financial losses and reducing vulnerability to poverty (Zheng and Peng 2021). The development of health insurance in Indonesia is inseparable from the health system, which aims to ensure that all people have access to quality and effective promotive, preventive, curative and rehabilitative health services, through social insurance mechanisms and the principle of equity by requiring every resident who can afford to do so to pay contributions, while those who cannot afford to pay contributions receive assistance from the government (Nasution et al 2020;Laksono et al 2021b;Wulandari and Laksono 2021).…”
Section: Introductionmentioning
confidence: 99%